Reference values for Doppler indices of the umbilical and fetal middle cerebral arteries in uncomplicated third trimester pregnancy - Paudel, S; Lohani, B; Gurung, G; Ansari, MA; Kayastha, P (Journal of Institute of Medicine Nepal, 2011)
Introduction: The purpose of this study was to categorize new reference ranges for measurements of commonly used umbilical artery and fetal middle cerebral artery Doppler indices (Pulsatility Index, Resistance Index, and Systolic: Diastolic ratio) in uncomplicated third trimester pregnancy. Methods: This was a prospective cross sectional study involving 101 singleton uncomplicated pregnancies of 30 to 37 weeks of gestation. Umbilical artery indices were obtained from free floating loop and middle cerebral Doppler indices were obtained from the proximal third of the artery with flow towards the probe. Regression equations were used to categorize reference ranges and percentile fitted Normograms were obtained for all the parameters. Results: Among 101 singleton pregnancies between 30 and 37 weeks of gestation, 65 (64.35%) were primigravida women and 36 (34.65%) were multigravida. Mean maternal age was 23.12years (range 16 to 35 years). Maximum number of pregnancies (18.81%) was at 34 weeks of gestation. The established percentiles of Doppler indices showed a continuous reduction of all the measured indices as pregnancy increases (p<0.0001). Conclusions: Reference ranges were obtained for the middle cerebral artery and umbilical artery Doppler indices. These ranges are consistent with similar studies done by other authors. Keywords: Doppler study; fetal Middle cerebral artery; pulsatility index; resistance index; systolic; diastolic ratio; umbilical artery DOI: http://dx.doi.org/10.3126/joim.v32i3.4953 Journal of Institute of Medicine, December, 2010; 32:3 5-13